Observation of the effect of intensity-modulated radiotherapy combined with microwave diathermy on tumor marker levels and prognosis in cervical cancer - Xiangdong Liu; Wei Li; Jie Zhou (Frontiers in Medicine)
ObjectiveThis study aimed to explore the effects of intensity-modulated radiation therapy (IMRT) combined with microwave diathermy (MWD) on tumor marker levels and prognosis in patients with cervical cancer.MethodsA retrospective analysis was conducted on the clinical data of 121 cervical cancer patients admitted to our hospital from April 2021 to April 2023. Among them, 59 patients received IMRT alone (IMRT group), while 62 patients received IMRT combined with MWD treatment (combination group). Comparison of disease control rates, serum tumor marker levels before and after treatment, quality of life (QoL), and prognosis between the two groups.ResultsThe combination group achieved a significantly higher disease control rate (88.71%) than the IMRT group (74.58%). After treatment, serum levels of carcinoembryonic antigen (CEA), squamous cell carcinoma antigen (SCCA), and carbohydrate antigen 50 (CA50) were significantly lower in the combination group than in the IMRT group (p < 0.05). Similarly, after treatment, serum levels of transforming growth factor-β (TGF-β), basic fibroblast growth factor (bEGF), and high-mobility protein A1 (HMGA1) were significantly reduced in the combination group than in the IMRT group (p < 0.05). After treatment, the improvement in the QoL in the combination group was significantly higher than that in the IMRT group (p < 0.05). Furthermore, the local recurrence rate (3.23%) and distant metastasis rate (1.61%) in the combination group were lower than those observed in the IMRT group (13.56% for both; p < 0.05).ConclusionCompared to IMRT alone, the combination of IMRT and MWD treatment for cervical cancer patients can significantly downregulate tumor markers and levels of TGF-β, bEGF, and HMGA1, increase tumor control effectiveness and patient QoL, and improve disease prognosis.